2014
DOI: 10.1080/17459435.2014.955590
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Black and White Accounts of 21st-Century Racial Profiling: Riding and Driving While Black

Abstract: Data from 60 qualitative interviews reveal the presence of racial tensions in 21st-century United States. Black participants expressed experiencing racial prejudice while operating automobiles. White passengers also reported witnessing instances of driving while Black (DWB) while riding with Black drivers. Specifically, White participants reported instances of profiling, where they witnessed Black drivers pulled over by police officers, although no traffic violation occurred. Two themes emerged for Black parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 17 publications
(20 reference statements)
4
8
0
Order By: Relevance
“…See Gideon'sArmy (2016). Similar examples and findings are reported elsewhere, see for example,Bell, Hopson, Craig and Robinson (2014).…”
supporting
confidence: 90%
“…See Gideon'sArmy (2016). Similar examples and findings are reported elsewhere, see for example,Bell, Hopson, Craig and Robinson (2014).…”
supporting
confidence: 90%
“…See Gideon'sArmy (2016). Similar examples and findings are reported elsewhere, see for example,Bell, Hopson, Craig and Robinson (2014).terms of use, available at https://www.cambridge.org/core/terms. https://doi.org/10.1017/bca.2017.23 Downloaded from https://www.cambridge.org/core.…”
supporting
confidence: 88%
“…Profiling also skews criminal justice statistics, which are used to inform policy decisions and can further harbor discrimination (Glaser, 2004). Studies continue to find that this racial profiling is played out in police automobile stops, as law enforcement officers are more likely to stop Black drivers than White drivers (Bell, Hopson, Craig, & Robinson, 2014; Lundman & Kaufman, 2003), which has resulted in Black drivers being fearful of being pulled over and then hoping to survive the interaction with law enforcement (Bell et al, 2014). Fridell and Lim (2016) analyzed use-of-force incidents by police officers and found that the implicit-bias perspective was more likely to explain police behavior than the counter bias perspective, which means that officer bias is likely to produce a greater tendency to use force against African American citizens.…”
Section: Literature Reviewmentioning
confidence: 99%